Lorentzian demodulation algorithm for multimode polymer optical fiber Bragg gratings - Mizuno, Yosuke; Ma, Tianyi; Ishikawa, Ryo; Lee, Heeyoung; Theodosiou, Antreas; Kalli, Kyriacos; Nakamura, Kentaro (My University, 2019)
For strain sensing applications, we develop a simple and accurate Lorentzian demodulation algorithm for fiber Bragg gratings (FBGs) inscribed in multimode optical fibers. As multimode FBG spectra generally exhibit multiple peaks, simply tracking some particular spectral peaks (i.†e., maximum detection) results in measurement failure when the strain is large. Here, using an FBG inscribed in a perfluorinated graded-index multimode polymer optical fiber, we experimentally evaluate the new method by comparing its performance with those of other demodulation algorithms, such as the maximum and centroid detection methods. Finally, using this method, we demonstrate the accurate measurement of strain of up to 1.0%.
Keywords: Cross-correlation; Sensor; Temperature